2003
DOI: 10.1111/j.1349-7006.2003.tb01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of the vascular endothelial growth factor receptor‐1 gene in prostate cancer

Abstract: Transcriptional silencing of cancer-related genes by DNA methylation is observed in various cancers. To identify genes controlled by methylation in prostate cancer, we used cDNA microarray analysis to investigate gene expression in prostate cancer cell lines LNCaP and DU145 treated with a methyltransferase inhibitor alone or together with a histone deacetylase inhibitor. We detected significant changes (3.4-5.7%) in gene expression in prostate cancer cell lines with the drug treatments. Among the affected gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…A previous study suggested promoter hypermethylation of Flt-1 as a possible modulating factor for Flt-1 expression in prostatic cancer. 17 However, the relationship between promoter methylation and expression of VEGF, Flt-1 and KDR had not been well elucidated in other cancers. The present negative correlation between promoter hypermethylation and VEGFR gene expression supports a model of epigenetic control of VEGFR gene expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested promoter hypermethylation of Flt-1 as a possible modulating factor for Flt-1 expression in prostatic cancer. 17 However, the relationship between promoter methylation and expression of VEGF, Flt-1 and KDR had not been well elucidated in other cancers. The present negative correlation between promoter hypermethylation and VEGFR gene expression supports a model of epigenetic control of VEGFR gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…16 In a previous study, aberrant promoter methylation of VEGFR1, Flt-1, was reported in prostatic cancer. 17 However, the promoter methylation status of VEGF and the VEGFR genes has not been well elucidated in other cancer types. In the present study, we evaluated the promoter DNA methylation status and related expression levels of VEGF and the VEGFR genes in different cancer cell lines and primary solid cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an autocrine function of VEGF on prostate cancer cell proliferation has been suggested by the demonstration of the high affinity receptors VEGFR-1 and VEGFR-2 on prostate cancer cells (74,75). VEGFR-1 has been found to be slightly expressed in PC-3 but not expressed in LNCaP and DU-145 cells (76).…”
Section: Discussionmentioning
confidence: 99%
“…We now know that VHL, VEGF and VEGF-R promoter activity is under the direct regulation of DNA-methylation (1,38,39,76). Ras oncogene induces a general demethylase activity in ras-transfected cells (77), promoting expression of many genes.…”
Section: -------------------------------------------------Marked Flucmentioning
confidence: 99%